Simon hoitoalueen metsänvartijat 1860-1905 - Lackman, Matti (1998)
Summary: Forest wardens in the Simo management district in 1860-1905.
Keywords: 1860-1905; metsänvartijat; historia; metsänhoito; valtionmetsät; torpparit; skogvaktare; historia; skogsskötsel; statens skogar; torpare; Simo; Simo